The role of the precuneus in metaphor comprehension: evidence from an fMRI study in people with schizophrenia and healthy participants - Mashal, Nira; Vishne, Tali; Laor, Nathaniel (Frontiers in Human Neuroscience, 2014)
Comprehension of conventional and novel metaphors involves traditional language-related cortical regions as well as non-language related regions. While semantic processing is crucial for understanding metaphors, it is not sufficient. Recently the precuneus has been identified as a region that mediates complex and highly integrated tasks, including retrieval of episodic memory and mental imagery. Although the understanding of non-literal language is relatively easy for healthy individuals, people with schizophrenia exhibit deficits in this domain. The present study aims to examine whether people with schizophrenia differentially recruit the precuneus, extending to the superior parietal cortex (SPL), to support their deficit in metaphor comprehension. We also examine interregional associations between the precuneus/SPL and language-related brain regions. Twelve people with schizophrenia and twelve healthy controls were scanned while silently reading literal word pairs, conventional metaphors, and novel metaphors. People with schizophrenia showed reduced comprehension of both conventional and novel metaphors. Analysis of functional connectivity found that the correlations between activation in the left precuneus/SPL and activation in the left PSTS were significant for both literal word pairs and novel metaphors, and significant correlations were found between activation in the right precuneus/SPL and activation in the right PSTS for the three types of semantic relations. These results were found in the schizophrenia group alone. Furthermore, relative to controls, people with schizophrenia demonstrated increased activation in the right precuneus/SPL. Our results may suggest that individuals with schizophrenia use mental imagery to support comprehension of both literal and metaphoric language. In particular, our findings indicate over-integration of language and non-language brain regions during more effortful processes of novel metaphor comprehension.